Analysis of Legal Considerations, Supreme Court Judge in Imposing A Life Sentence in Premeditated Murder Case (Case Study of Decision 813/K/Pid/2023) - Bagus Dwi Yulianto; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2025)
The premeditated murder case of the defendant Ferdy Sambo (FS), who killed Brigadier Nofriansyah Yoshua Hutabarat (Brigadier J) in July 2022, has attracted the attention of the Indonesian people. This was initially thought to be a shootout between the victim and Bharada Richard Eliezer (Bharada E), who allegedly sexually harassed FS's wife. However, further investigation showed that FS planned the murder and ordered Bharada E to shoot Brigadier J. FS, who was charged with Article 340 of the Criminal Code on premeditated murder and Article 49, juncto Article 33 of the ITE Law, as well as Article 55 of the Criminal Code. This case attracted attention because law enforcement officials, who were supposed to be responsible for maintaining security and order, were instead involved in criminal acts. FS was sentenced to death by the South Jakarta District Court during the sentencing process. Still, at the cassation level, the Supreme Court changed the sentence to life imprisonment, after Law No. 1 of 2023, which made the death penalty a special penalty and affirmed the importance of more rehabilitative penal goals, political changes in Indonesia's criminal law became part of the consideration of Supreme Court judges. The defendant's emotional factors, his life history, and his thirty years of service in the National Police were also considered by the judge. Nevertheless, FS's actions are still considered unlawful, so punishment cannot be avoided. Considering all relevant aspects, this decision demonstrates the application of the principle of proportional justice.